Analysis of Psychological Capital on Employee Adaptability in Organizations Undergoing Change (Psikologiya Journal, 2025)
This study examines the influence of psychological capital on employee adaptability in organizations undergoing change by integrating psychological, organizational, and technological perspectives. Using a mixed-method approach that combines conceptual analysis with secondary data from global workforce surveys and national organizational reports, the study highlights how hope, efficacy, resilience, and optimism shape adaptive behavior in transformation contexts. The findings demonstrate that employees with high psychological capital display stronger motivation, emotional stability, and proactive engagement, enabling them to respond effectively to challenges posed by digital transformation, restructuring, cultural shifts, and leadership transitions. Psychological capital promotes cognitive flexibility and constructive interpretation of uncertainty, thereby supporting sustained adaptation. The study identifies contextual moderators such as leadership quality, organizational climate, and the nature of change, which influence how psychological capital translates into adaptive behavior. Strategic recommendations emphasize the importance of psychological capital development through structured training, transformational leadership, supportive systems, continuous learning cultures, and well-being programs. Overall, the study provides a comprehensive understanding of how psychological capital can enhance workforce adaptability and strengthen organizational capacity during periods of change